2015
DOI: 10.3906/elk-1402-66
|View full text |Cite
|
Sign up to set email alerts
|

A statistical analysis of wind speed data using Burr, generalized gamma, and Weibull distributions in Antakya, Turkey

Abstract: Abstract:The wind energy potential of the Antakya area was statistically analyzed based 8 years of wind data sets (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009). The 4-parameter Burr, 3-parameter generalized gamma, and conventional Weibull distributions were regarded as suitable statistical models for describing wind speed profiles. The suitability of the models was tested by R 2 , RMSE, chi-squared, and Kolmogorov-Smirnov analysis. According to goodness-of-fit tests, the Burr distribution was found to be mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 25 publications
(25 reference statements)
0
28
0
1
Order By: Relevance
“…As the FTT scheme uses a constant threshold for all β values, the gap between MILP and FTT is larger for larger β and moderate Q av values. A typical value for β is reported to be less than 1 in [11]. Moreover, for high Q av , battery capacity dominates the outage performance, and FTT again attains the MILP solution for all β values.…”
Section: Proposed Heuristic Transmission Schemementioning
confidence: 86%
“…As the FTT scheme uses a constant threshold for all β values, the gap between MILP and FTT is larger for larger β and moderate Q av values. A typical value for β is reported to be less than 1 in [11]. Moreover, for high Q av , battery capacity dominates the outage performance, and FTT again attains the MILP solution for all β values.…”
Section: Proposed Heuristic Transmission Schemementioning
confidence: 86%
“…The utilization rate of renewable sources is 20% these days and this level is planned to be increased by 50% to a level of 30% over the next two years [1]. Renewable energy sources include biomass [5], geothermal [6], solar [7] and the wind [8,9]. Biogas is also one of the most important renewable energy fuels which is produced by anaerobic digestion of organic based wastes [10].…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that Weibull, Rayleigh, and gamma distributions represent the data better. Mert and Karakuş [17] employed 4-parameter Burr, 3-parameter generalized gamma, and Weibull distributions to analyze wind speed data obtained from Hatay, Turkey. Arslan et al [18] proposed generalized Lindley and power Lindley distributions as alternative to Weibull distribution.…”
Section: Introductionmentioning
confidence: 99%